Synchronous adenomyomas of the ileum in an adult‐an exceptional cause of intussusception. Issue 7 (20th May 2015) - Khmou, Mouna; Znati, Kaoutar; Zouaidia, Fouad; Jahid, Ahmed; Bernoussi, Zakiya; Mahassini, Najat
Key Clinical Message In this article, we report a case of two synchronous ileal adenomyomas leading to intussusception. This rare occurrence has never been reported in the literature. Our case is noteworthy, because the lesion is rare and should be considered in the differential diagnosis of intussusception in adults.